Islam’s inclusion in Spain as seen from Catholic social teaching - Villagrán, Gonzalo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
If we consider Catholic social teaching as a tradition of social thought based on Christian revelation, this teaching’s reflection on Islam is already the beginning of interreligious dialogue. Catholic social teaching’s position on the inclusion of Islam is based on a main assertion, human dignity, developed then in the principles of religious freedom and the common good, as well as in dialogue as a main characteristic of its way of proceeding. These traits design a view of society similar to a moderate communitarianism. From this point of view we can evaluate the Spanish inclusion model, strongly inspired by Catholic social thought. In fact, the Spanish model follows closely these main principles. However, we can also notice how this model drifts apart from Catholic social teaching as it does not demand the State to protect an objective common good or to promote interreligious dialogue. These can be the lines of the development of the model in the future.